The Last Song - Sato, Yumiko (Voices: A World Forum for Music Therapy, 2010)
Through my work as a hospice music therapist I’ve come to believe that people who are dying have an inner awareness of their own impending deaths. When I was a music therapy intern, I met a patient who was the first to reveal to me this inner awareness of death’s approach. This is a story of Herb, a former singer, whose life was filled with music. As his Alzheimer’s disease got worse, the only thing that comforted him was music. By singing his last song one day he taught me the mystery of dying.